The Role of Midwives in the Early Detection of Infertility Risk Factors Among Women of Reproductive Age - Kurniawati, Erna Yovi; Iriyani, Elfrida (Ilmu Bersama Center, 2025)
Primary infertility is an increasingly prevalent reproductive health issue, yet it often remains undetected at the primary care level. Midwives, as frontline health professionals, hold strategic potential in the early identification of infertility risk through maternal and child health (MCH) services. This study aimed to analyze the relationship between patients’ perceptions of midwives’ roles and the identification of infertility risk factors among couples of reproductive ages. This study employed a cross-sectional design with a quantitative approach. The sample consisted of 32 reproductive-age couples attending MCH services in Yogyakarta, Indonesia. Data were collected using a structured questionnaire assessing perceptions of midwives’ roles across five dimensions: education, early detection, counseling, referral, and communication. Data analysis included chi-square tests and multivariate logistic regression. A significant association was found between positive perceptions of midwives’ roles in education (p=0.041), early detection (p=0.018), and communication (p=0.029) with successful identification of infertility risk factors. Early detection emerged as the most dominant factor (OR=3.47; 95% CI=1.29–9.31). Midwives' roles in early detection, education, and communication significantly contribute to identifying infertility risk factors. Strengthening midwives’ authority and capacity in fertility-related issues is essential to promote a sustainable preventive approach in primary health care.